(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
In a web of texts, we present reflections on practices for a Body-without-organs involving the writing of letter-performances. In a cartographic approach, the research path created modes of writing and layered images of the bodies that took part in it. The main objective of the research was to produce letter performances and connections between bodies. The participants wrote letters and produced intensities that were shown during the discussion. Deleuze and Guattari’s Philosophy of Difference provided the conceptual basis for analyzing letter performances with expanding lines and movements. In the end, the intensities of the maps of connections and affections between bodies formed other maps.